Decreased initial compound muscle action potential amplitudes in myasthenia gravis. Issue 5 (22nd August 2022) - Kojima, Yuta; Shibuya, Kazumoto; Uzawa, Akiyuki; Kano, Hiroki; Nakamura, Keigo; Yasuda, Manato; Suzuki, Yo‐ichi; Tsuneyama, Atsuko; Suichi, Tomoki; Ozawa, Yukiko; Misawa, Sonoko; Noto, Yu‐ichi; et al.
Abstract: Objective: We aimed to investigate the hypothesis that amplitudes of compound muscle action potential (CMAP) elicited by single stimulation decrease by baseline neuromuscular blocking in myasthenia gravis (MG), and to examine correlation of CMAP amplitudes with baseline muscle weakness. Methods: One hundred ninety‐four consecutive patients who underwent repetitive 3 Hz nerve stimulation tests (RNST) at our laboratory were included in the study. Of these, 109 patients were diagnosed as suffering from MG, and the remaining 85 with other disease served as the non‐MG controls. RNST was performed on the nasalis, trapezius, and abductor digiti minimi (ADM) muscles. CMAP amplitudes elicited by the first stimulation were compared between the two groups. In MG patients, we studied the correlation of CMAP amplitudes with MG Foundation of America (MGFA) class, total scores of manual muscle testing (MMT), and 4th decrement (%) of RNST. Results: Compound muscle action potential amplitudes in MG were significantly lower than in controls ( p  < 0.05 in all muscles tested). Decreases in CMAP amplitudes were more prominent in generalized than in ocular MG ( p  < 0.05), and in patients with MGFA III–V classes than in those with 0–II ( p  < 0.01 in the trapezius and ADM). CMAP amplitudes partially correlated with total MMT scores and MG‐ADL scale scores. Additionally, CMAP amplitudes elicited by the first stimulation correlated with the 4th decrement of RNST ( p  < 0.01 in all muscles tested). Conclusion: Compound muscle action potential amplitudes are reduced in MG, presumably by baseline neuromuscular transmission block, and could reflect persistent muscle weakness, rather than fatigue, in MG patients.